Beyond the use of food supplements: An empirical analysis in Italy - A. LOMBARDI; F. VERNEAU; P. LOMBARDI (Chiriotti Editori, 2016)
This paper aims to profile Italian food supplements used by consumers based upon their psychometric patterns and demographic characteristics. The FTNS scale is used to assess empirically and evaluate the role of technophobic/technophilic consumer traits in determining the decision whether or not to consume supplements and vitamins and the frequency of their consumption. An ad-hoc survey was carried out in 2012 involving 400 residents of a metropolitan area in southern Italy. Our results show that women have a higher consumption frequency of dietary supplements, while age, BMI and education influence the propensity to consume. As regards food habits, the propensity to use dietary supplements is positively associated to the consumption of bread and pasta, red meat and pulses, and negatively with the consumption of fruit and cheese. Finally, the research supports the role of technophobic traits as consistent and significant determinants of the consumption frequency of dietary supplements.